Corporate social responsibility practices by public limited construction firms in Malaysia - Suzana C. Alih, 1987- author; Christopher Nigel Preece supervisor; Sarajul Fikri Mohamed, supervisor; Fakulti Alam Bina (2014)
Thesis (Sarjana Sains (Ukur Bahan)) - Universiti Teknologi Malaysia, 2014